KINERJA PERAWAT DALAM PELAKSANAAN PENCEGAHAN RISIKO JATUH DI RUANG RAWAT INAP ANAK - Heri Saputro (Universitas STRADA Indonesia, 2016)
Genesis falls pediatric patients in the treatment room is often not reported because it is considered as the future development of the child's learning. Results of a preliminary study of the pediatric ward was found not installed warning risk of falls in children (both sticker and risk alert bracelet), even if the child has a high risk score fell, parents ofte n forget to raise the hand rail on the bed. The incidence of falls in children are not separated from the role of nurses and parents. This study identifies nurses' performance on the implementation of risk prevention fall in inpatient children, with a single case design and purposive sampling technique. The study was conducted in 9 IRNA Dr Sardjito. Collecting data by direct observation and focus group interviews. Explanatory descriptive analysis of data, analyzed by content analysis. Results observation approximated 52.8% of pediatric patients in the guard room nurses and 36.1% rooms with doors that open in pediatric patients at high risk of falling. Results obtained group discussions nurse performance is influenced motivation, supervision and incentives.